As práticas e representações de leitura dos detentos alfabetizadores e alfabetizados do Complexo Prisional de Aparecida de Goiânia - SILVA NETO, Antonio Artequilino da (2009)
This present dissertation related to the line of research Teaching Staff Formation and Professionalization analyzes the practices and the representations of those teachers and learners prisoners in the Prison Complex of the Aparecida de Goiânia, in a context which the population of the prison is involved and it is constituted majority by stigmatized individuals according to a society that in a paradox way, at the same time, oppresses and fears them. Most of them are excluded and marginalized, without schooling and come from poor and unprotected social conditions. The research has as a goal to analyze the speech of those prisoners that have participated of a process of literacy inside the Prison Complex of the Aparecida de Goiânia, in a period of time from July 2007 to June 2008, the process of understanding their practices and their representations of reading, it was considered as a privileged source the proper speech of the teachers and learners inside the carcere environment. It is a qualitative research wich the methodology and the theory content are based on the analyze of the discursive representations from studies by Bakhtin, Vygotsky, Foucault, Goffman, Bourdieu, Certeau, Freire and Chartier, among many others authors who also helped to base scientifically the results and the evidences carried out along this research. The data collected in order to make the analyze, took place inside the Prison Complex of the Aparecida de Goiania, and it includes the Provisional Prison House (Casa de Prisão Provisória) and the Prison Coronel Odenir Guimarães (Penitenciária Odenir Guimarães) located in the city of Aparecida de Goiania, in the state of Goias, they were collected from experiences lived along and after the time when those literacy tasks were happening. After selecting a sample for the qualitative research, semi structured interviews were carried out and recorded with sixteen prisoners, eight of them performed as teachers and eight were considered learners. The analyze of the practices and representations of young and adult reading, deprived of freedom pointed out that even under the bad conditions that the research was carried out, it was possible to teach reading and writing 64% of this group of prisoners, and also they still have a great search through the world of reading by keeping themselves studying.The analyses has also demonstrated that the bad and precarious conditions of the carcere interferes in the process of teaching and learning, as a result the readers were banned of the activity of reading. In this sense, the research points out the need of encouragement of habits of reading in a proper environment, formal and informal, as a component of a public policy aimed to young and adults education inside prison sites, not only in Aparecida de Goiânia, as well as in any other city in Brazil